PENGEMBANGAN MODUL MATEMATIKA BERBASIS MASALAH UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIK SISWA - Masdelima Azizah Sormin; Nursahara Nurasahara (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2019)
This research is a development research using a modification between the 4-D development model developed by Thiagarajan. The stages of this research are define, design, develop and disseminate . The development of problem-based mathematical modules at the disseminate (dissemination) was   carried out in a limited manner in schools that are the subject of research.   The   subjects   in   this   study   were   class   X   students   of   SMA   Negeri   4Padangsidimpuan. From the results of the development test: (1) problem-based mathematics modules fulfiill validity criteria with valid predicates, (2) the problem-based mathematics modules was practical based on revised and interview results from the expert teams, and (3) this  problem-based  mathematics modules was effective to used based on observations the time ideal of percentage achievemen , the results of the mathematical problem solving ability test fulfill classical completeness, that was 80% of the test subjects, and (4) the improvement of students' mathematical problem solving skills by using the module from test I to trial II and fulfill the classical completeness. Keywords:  Development,  Problem  Based  Mathematics  Module,  Mathematical  ProblemSolving Ability